Effectiveness of Lemon Solution Gargling in Reducing Dental Plaque Index among Senior High Students at Porong, Indonesia - Sealomita Rizka Apritama; Bambang Hadi Sugito; Imam Sarwo Edi; I Gusti Ayu Kusuma Astuti N (International Journal of Advanced Health Science and Technology, 2024)
Efforts to overcome dental and oral health problems and improve oral hygiene can be done by preventing and eliminating plaque accumulation. Efforts to prevent the appearance of plaque are called plaque control. The results of examining the PHP index in class 11 of SMA Negeri 1 Porong showed that 5 out of 10 respondents had a bad plaque index with a prevalence of 50% with an average PHP index of 3.54. High PHP index. The aim of this research is to determine the effectiveness of gargling using lemon solution with levels of 10% and 15% in reducing the dental plaque index in class 11 students of SMA Negeri 1 Porong in 2024. This type of research is Pre-Experimental research with One Group Pretest Posttest with a sample of students Class 11 of SMA Negeri 1 Porong, totaling 52 students. The data collection instrument used was an examination sheet to measure the PHP index. The analysis technique uses an unpaired T test (Independent T-Test). The test results from the research obtained a ρ value of 0.108 or a significant ρ score above α (0.05). The conclusion from this study is that there is no difference in the effectiveness of gargling using lemon solution with levels of 10% and 15%.